The Mutual Effects of Perceived Spiritual Needs on Quality of Life in Patients With Advanced Cancer and Family Caregivers. Issue 4 (August 2021) - Huang, Li-Ting; Tai, Chun-Yi; Longcoy, Joshua; McMillan, Susan C.
Abstract : Perceived spiritual needs may increase when patients with advanced cancer and their family caregivers are confronted with the challenges of physical and psychological distress. Given the intertwined relationships between patients and family caregivers, their interdependence should be considered to understand how perceived spiritual needs affect the quality of life of their own and of their partner. This study used the Actor-Partner Interdependence Model as the conceptual model to investigate the mutual effects of perceived spiritual needs on the quality of life in patients with advanced cancer and their family caregivers after being admitted to hospice. This cross-sectional study used the baseline data of a large clinical trial and identified that patients with cancer and their family caregivers perceived similar spiritual needs associated with the community and outlook needs and had fewer unmet spiritual needs. After controlling for partner effects, perceived outlook needs shown in patients significantly predicted their own functional well-being and social/spiritual well-being. Outlook and community needs perceived by family caregivers also significantly predicted their own mental health. Although partner effects were not shown as expected, the findings provide insight into the mutuality of spirituality and demonstrate the necessity of providing timely and ongoing spiritual assessment and care.